Insurance status and head and neck radiotherapy interruption disparities in the Mid‐Southern United States. Issue 8 (6th March 2020) - Yarn, Charles; Wakefield, Daniel V.; Spencer, Sharon; Martin, Michelle Y.; Pisu, Maria; Schwartz, David L.
Abstract: Background: Relationships between health insurance coverage and radiotherapy (RT) interruption rates in patients with head and neck (H&N) cancer remain unclear. Methods: We performed a retrospective cohort study at our academic center. Days of RT interruption for individual patients were tabulated, analyzed for explanatory variables, and geographically mapped. Results: 894 of 7526 (11.9%) scheduled treatment days were interrupted, impacting 149 of 216 (69%) patients. Medicaid/uninsured patients experienced a 7.3 day mean interruption (SD = 9.9) vs 3.4 days (SD = 5.2) for Medicare/private patients ( P < .001). RT interruption was predicted by insurance status in multivariate analysis ( P = .008). Higher RT interruption rates overlapped geospatially with low predicted median household income and racial minority neighborhoods. Conclusion: Unplanned treatment interruptions are a key source for H&N RT quality shortfalls in Medicaid/uninsured patients. This is the first geographic benchmarking of H&N RT delivery disparities across a complete metropolitan region, and will guide interventions studies to reduce interruption risk.